2014
DOI: 10.1021/cm5012845
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Electrochemical Performance of the Orthorhombic Li2Fe(SO4)2 Polymorph for Li-Ion Batteries

Abstract: To enhance the safety, cost, and energy density of Li-ion batteries, significant research efforts have been devoted to the search for new positive electrode materials that exhibit high redox potentials and are composed of low-cost, earth-abundant elements. Sulfate chemistry has yielded promising results for iron-based polyanionic electrode materials using the FeIII+/FeII+ redox couple, including the recent discovery of a monoclinic marinite Li2Fe­(SO4)2 phase (3.83 V vs Li+/Li0). Here, we report the ball-milli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 39 publications
5
71
0
Order By: Relevance
“…SO 4 ‐based compounds are known to present a rich crystal chemistry and often occur as polymorphs (e. g. tavorite/triplite LiFeSO 4 F, tavorite/layered LiFeSO 4 OH). This is also the case for Li 2 Fe(SO 4 ) 2 , where besides the monoclinic phase an orthorhombic counterpart was reported, which is isostructural to Li 2 Ni(SO 4 ) 2 . Orthorhombic Li 2 Fe(SO 4 ) 2 is prepared via a mechanochemical approach, where FeSO 4 and Li 2 SO 4 are intensively ball‐milled for 10 h. A similar protocol was also applied for the synthesis of other orthorhombic Li 2 M (SO 4 ) 2 ( M =Co, Zn, Ni) homologues.…”
Section: Li‐based Sulfatesmentioning
confidence: 99%
“…SO 4 ‐based compounds are known to present a rich crystal chemistry and often occur as polymorphs (e. g. tavorite/triplite LiFeSO 4 F, tavorite/layered LiFeSO 4 OH). This is also the case for Li 2 Fe(SO 4 ) 2 , where besides the monoclinic phase an orthorhombic counterpart was reported, which is isostructural to Li 2 Ni(SO 4 ) 2 . Orthorhombic Li 2 Fe(SO 4 ) 2 is prepared via a mechanochemical approach, where FeSO 4 and Li 2 SO 4 are intensively ball‐milled for 10 h. A similar protocol was also applied for the synthesis of other orthorhombic Li 2 M (SO 4 ) 2 ( M =Co, Zn, Ni) homologues.…”
Section: Li‐based Sulfatesmentioning
confidence: 99%
“…The NPD patterns were refined against the orthorhombic structure (space group Pbca) initially proposed by Isasi et al for the nickel analogue Li 2 Ni(SO 4 ) 2 and as previously reported by our group. 17,20,24 The results of these refinements as well as their structures are summarized in Figure SI1-2 and Table SI1-3 (Supporting Information). The structural models derived from XRD were here fully confirmed by NPD measurements indicating that the structures were preserved between room temperature and the above-mentioned temperatures.…”
Section: Crystal Structuresmentioning
confidence: 99%
“…29 However, in the present case, we could not identify any monoclinic distortion based on the Rietveld refinements of the XRD patterns of Li 2 Fe(SO 4 ) 2 and Li 1.5 Fe(SO 4 ) 2 . 17 Indeed, the Bragg peaks present an intrinsic broadening caused by the mechano-chemical synthesis approach, and refining the structural model in a monoclinic symmetry is almost impossible as the number of parameters is increased a lot and they may be highly correlated.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…Anyhow, many great successes of the fundamental understanding have been achieved based on the advanced characterization methods and technological optimizations . Various sodium‐insertion compounds have been studied for the cathode materials to NIBs, including layered oxides, tunnel oxides, olivine/sodium (Na) super ionic conductor (NASICON)‐structure phosphates, and polyanionic‐structure compounds . NaCoO 2 as an analog of LiCoO 2 (the current start‐of‐the‐art cathode material for LIBs) was the first reported layered oxides (Na x MeO 2 , Me = transition metal elements) for NIB cathode materials .…”
Section: Introductionmentioning
confidence: 99%